Application of Reverse Genetics in Functional Genomics of Potyvirus - Maathavi Kannan (Viruses, 2020)
Numerous potyvirus studies, including virus biology, transmission, viral protein function, as well as virus–host interaction, have greatly benefited from the utilization of reverse genetic techniques. Reverse genetics of RNA viruses refers to the manipulation of viral genomes, transfection of the modified cDNAs into cells, and the production of live infectious progenies, either wild-type or mutated. Reverse genetic technology provides an opportunity of developing potyviruses into vectors for improving agronomic traits in plants, as a reporter system for tracking virus infection in hosts or a production system for target proteins. Therefore, this review provides an overview on the breakthroughs achieved in potyvirus research through the implementation of reverse genetic systems.